ANALISIS OVERREACTION PADA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2015-2017 - Eko Krida Zafran Zakir R.; Afifudin Afifudin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research aims to investigate the overreaction occurrence in Average Cumulative Abnormal Return (ACAR) of the winner and loser of the superinvestor portofolios and the ACAR difference in both portfolios. This research is a correlational study with a quantitative approach. Secondary data were the stock data of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2017. The sampling technique was Purposive sampling and obtained a total sample of 126 companies. Data were analyzed statistically by using One Sample t-Test. The result demonstrates the significance value (p-value) of the ACAR overreaction data of winner portofolio, loser, and the difference in ACAR values of 0.024, 0.026, and 0.018 (<α 0.05), respectively. The cumulative value of abnormal returns reached an average of 1,195245. Based on the findings, it can be stated that there was no overreaction in the ACAR winner portfolio, and the winner's shares still produce a positive return. On the other hand, even though there was no overreaction ACAR of the loser portfolio, losers shares still produce a negative return (loss). In addition, overreaction was not found in the ACAR difference between winner and loser portfolios. Therefore, it is concluded that the loser portfolio performance did not outperform the winner portfolio performance during the study period. Market overreaction anomalies do not occur on the Indonesia Stock Exchange in the period 2015-2017, and indicate that the stock market on the IDX has been efficient yet in weak form.Keywords: Overreaction, Stock, Manufacturing companies, BEI.